Relativistic Electron Precipitation Near Midnight: Drivers, Distribution, and Properties. Issue 1 (13th January 2022) - Capannolo, L.; Li, W.; Millan, R.; Smith, D.; Sivadas, N.; Sample, J.; Shekhar, S.
Abstract: We analyze the drivers, distribution, and properties of the relativistic electron precipitation (REP) detected near midnight by the Polar Orbiting Environmental Satellites (POES) and Meteorological Operational (MetOp) satellites, critical for understanding radiation belt losses and nightside atmospheric energy input. REP is either driven by wave‐particle interactions (isolated precipitation within the outer radiation belt), or current sheet scattering (CSS; precipitation with energy dispersion), or a combination of the two. We evaluate the L‐MLT distribution for the identified REP events in which only one process evidently drove the precipitation (∼10% of the REP near midnight). We show that the two mechanisms coexist and drive precipitation in a broad L ‐shell range (4–7). However, wave‐driven REP was also observed at L < 4, whereas CSS‐driven REP was also detected at L > 7. Moreover, we estimate the magnetotail stretching during each REP event using the magnetic field observations from the Geostationary Operational Environmental Satellite (GOES). Both wave‐particle interactions and CSS drive REP in association with a stretched magnetotail, although CSS‐driven REP potentially shows more pronounced stretching. Wave‐driven REP events are localized in L shell and often occur on spatial scales of <0.3 L . Using either proton precipitation (observed by POES/MetOp during wave‐driven REP) as a proxy for electromagnetic ion cyclotron (EMIC) wave activity or wave observations (from GOES and the Van Allen Probes) at the conjugate event location, we find that ∼73% wave‐driven REP events are associated with EMIC waves. Plain Language Summary: Relativistic electrons are typically stably trapped in the outer radiation belt that surrounds the Earth at distances from ∼3–4 Earth radii ( R E ) up to 7–8 R E . However, magnetospheric plasma waves can potentially interact with electrons, causing them to precipitate into the Earth's atmosphere. Electron precipitation also occurs when the magnetic field lines are stretched away from the Earth such that their curvature radius is comparable to the gyroradius of the electrons. Here, we specifically focus on precipitation events that occur near midnight. We categorize events by the driver (waves or field line stretching) depending on the shape of precipitation observed at low Earth orbit. We find that the two mechanisms overall overlap. We also show that relativistic electron precipitation (REP) is associated with field line stretching for both mechanisms and that most of the wave‐driven precipitation is caused by a specific type of plasma waves, called electromagnetic ion cyclotron waves. Our findings are critical for understanding the driver of REP events near the midnight sector, which is important to account for radiation belt losses, as well as for quantifying the source of the energy input into the Earth's atmosphere that subsequently affects the atmospheric chemistry and conductivity. Key Points: We use polar orbiting environmental satellites data to analyze the relativistic electron precipitation (REP) near midnight (22‐02 magnetic local time), which is found to occur over L ∼ 4–7 We study REP events due to a single driver: waves (isolated REP) or current sheet scattering (energy‐dependent precipitation) Both mechanisms drive precipitation during field line stretching and most wave‐driven events occur in association with electromagnetic ion cyclotron waves